The Use Of Indonesian English Code Mixing In Social Media Networking (Facebook) By Indonesian Youngsters - Sutrismi, Sutrismi; , Agus Wijayanto, Ph.D; , Dra. Malikatul Laila, M. Hum (2014)
This research investigates the use of code mixing in social media networking (Facebook) by Indonesian youngsters. The study aims to describe 1) the types of code mixing and 2) the reasons of using code mixing in social media networking (Facebook) by Indonesian youngsters. This research applies descriptive qualitative method. The data of this research are Indonesian - English code mixing in Indonesian Facebook users posting and the information of the reasons of using code mixing. The data are taken from the Indonesian Facebook users posting and interviewing by chatting. The way to collect data is observation and documentation method. The data are analyzed base on the linguistic form of code mixing by Suwito's theory and the reasons of code mixing by Hockett's theory. The results show that there are six types of linguistic forms of code mixing consist of 48 data or 63,16 % of word (40 data single word and 8 data compound word), 1 datum or 1,32 % of blending , 7 data or 9,21 % of hybrid, 2 data or 2,63 % of word reduplication, 14 data or 18,42 % of phrase (9 data of noun phrase, 4 data of verb phrase, and 1 datum of preposition phrase) and 4 data or 5,26 % of clause. The second results are the reason of using code mixing. The result show that there are 7 data or 14 % for need filling motive, there 4 data or 8 % for prestige filling motive, and 39 data or 78 % for other reasons ((a) to make simple and familiar, (b) to show personal habit, (c) to stress the message, (d) to practice English, (e) to show the trend, (f) to match with the situation, (g) to show their prestige and (h) to differentiate with others).